The Curious Incident of Autism Myths in The Portrayal of an Autistic Character - Muhammad Fuad Alfansi (Passage, 2018)
This paper aims to investigate the portrayal of an autistic character in relation to autism myths in the novel written by Mark Haddon in 2003 entitled The Curious Incident of the Dog in the Night-time. Autistic characters have gained considerable attention in many contemporary literary works. Within the realm of autism myths and method of textual analysis, the main character in The Curious Incident of the Dog in the Night-time (2003) was analyzed to see if it is constructed on the stereotypical autistic character. It is found that the autistic character in the novel is portrayed as an autistic child who has a tendency to avoid social contact with others, independent, affectionate and has special talent and savant skill. Moreover, the study also reveals that the portrayal of an autistic character in the novel confirms three myths of autism but negates four other myths. These findings show that current literary works still rely on the myths of autism that are formed by society to portray an autistic character. Keywords: autism, autistic character, myths of autism, portrayal